Asymmetric modified silicon dioxide particle doped sulfonated polyetheretherketone membrane as well as preparation method and application thereof

By doping asymmetrically modified silica particles in the sulfonated polyether ether ketone film, the problems of high swelling, ion selectivity and poor proton conductivity of the film are solved, and higher mechanical and thermal stability and proton conductivity are achieved, thereby improving the performance of the flow battery.

CN119552399AActive Publication Date: 2025-03-04CHINA NAT PETROLEUM CORP

Patent Information

Application Number
CN202311119693.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-04
Estimated Expiration
2043-09-01

AI Technical Summary

Technical Problem

The existing sulfonated polyether ether ketone film has high swelling properties, poor ion selectivity and proton conductivity, and cannot meet the high performance needs of flow batteries.

Method used

By doping asymmetrically modified silica particles in the sulfonated polyether ether ketone film, hydrogen bonds are formed with hydroxyl groups and sulfonated polyether ether ketone, mechanical and thermal stability are increased, and proton conductivity is improved by grafting the sulfonic acid group.

Benefits of technology

It significantly reduces the swelling of the membrane, improves its ion selectivity and proton conductivity, extends the service life of the membrane, and improves the overall performance of the flow battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an asymmetric modified silicon dioxide particle doped sulfonated polyether ether ketone membrane and a preparation method and application thereof, the preparation method comprises the following steps: (1) under a heating condition, mixing surface hydroxylated silicon dioxide particles and paraffin, adding a first solvent, stirring, and cooling to obtain paraffin emulsion droplets; (2) mixing the paraffin emulsion droplets obtained in the step (1) with a sulfydryl-containing silane coupling agent, and reacting to obtain a mixture; and mixing the mixture with a hydrogen peroxide solution, and carrying out oxidation reaction to obtain the asymmetrically modified silicon dioxide particles, and (3) mixing the asymmetrically modified silicon dioxide particles and sulfonated polyetheretherketone, and drying to obtain the asymmetrically modified silicon dioxide particle doped sulfonated polyetheretherketone membrane. The asymmetric modified silicon dioxide particle doped sulfonated polyether ether ketone membrane provided by the invention is low in swelling property, relatively high in proton conductivity and relatively good in ion selectivity, and the performance of a flow battery can be improved when the membrane is used for the flow battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy materials, and specifically relates to an asymmetrically modified silica particle-doped sulfonated polyetheretherketone membrane and a preparation method and application thereof. Background Art

[0002] Large-scale and efficient use of renewable energy sources (such as solar and wind) can significantly address the rapidly growing energy needs of modern society while alleviating resource limitations and environmental issues of fossil fuels. Long-duration energy storage technology will play an increasingly important role in the grid connection of intermittent and unstable renewable energy generation, improve the reliability and affordability of power generation systems, fill seasonal energy storage solutions, and reduce the cost of wind-solar battery power systems. Liquid flow batteries are considered to be a promising long-duration energy storage technology with the advantages of fast response, power and capacity decoupling, long cycle life, and environmental friendliness, making them very suitable for large-scale electrochemical energy storage.

[0003] As one of the key materials of liquid flow batteries, ion exchange membranes are used to separate cathode and anode electrolytes and transfer conductive ions. An ideal ion exchange membrane should have the characteristics of low cost, good proton conductivity, high ion selectivity, good chemical and mechanical stability, etc., which is crucial to the cycle life and efficiency of the battery. The currently commercialized liquid flow battery perfluorosulfonic acid ion exchange membrane (Nafion) has the advantages of good chemical stability and thermal stability, high conductivity, and high mechanical strength, but the high cost (US$500-700 per square meter) and low ion selectivity have hindered the commercialization of liquid flow batteries. The sulfonated polyetheretherketone membrane material has high ion selectivity, low cost, and excellent chemical and mechanical stability. CN104209023A blends uniformly sulfonated silica microspheres with sulfonated polyetheretherketone to prepare a hybrid membrane, which is applied to CO2 / CH4 gas separation and has high selectivity and permeability, but the hydrogen bonding between the sulfonated silica microspheres and the sulfonated polyetheretherketone is weakened, which increases the swelling of the hybrid membrane and is not suitable for liquid flow battery ion exchange membranes. CN10980285A disperses and wraps uniformly sulfonated nano-silica in a sulfonated polyetheretherketone membrane, ensuring the thermal stability of the sulfonated polyetheretherketone membrane. However, the nano-silica particles are too small to ensure the ion conductivity and ion selectivity of the hybrid membrane, and are not suitable for ion exchange membranes of liquid flow batteries.

[0004] In summary, the existing sulfonated polyetheretherketone membrane has high swelling properties and poor ion selectivity and proton conductivity. Therefore, there is an urgent need to develop a high-performance sulfonated polyetheretherketone membrane that can improve the performance of flow batteries when used in flow batteries. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an asymmetric modified silica particle doped sulfonated polyetheretherketone membrane and its preparation method and application. By designing the doping material of the sulfonated polyetheretherketone membrane, the ion selectivity and proton conductivity of the sulfonated polyetheretherketone membrane are improved, the swelling of the sulfonated polyetheretherketone membrane is reduced, and its service life is extended, thereby effectively improving the comprehensive performance of the sulfonated polyetheretherketone membrane for liquid flow batteries.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing an asymmetrically modified silica particle doped sulfonated polyetheretherketone membrane, the preparation method comprising the following steps:

[0008] (1) under heating conditions, mixing surface hydroxylated silica particles and paraffin, adding a first solvent, stirring, and then cooling to obtain paraffin emulsion droplets;

[0009] (2) mixing the paraffin emulsion droplets obtained in step (1) and the mercapto-containing silane coupling agent and reacting them to obtain a mixture; mixing the mixture with a hydrogen peroxide solution and then performing an oxidation reaction to obtain the asymmetrically modified silica particles;

[0010] (3) The asymmetrically modified silica particles and sulfonated polyetheretherketone are mixed and dried to obtain the asymmetrically modified silica particles doped with sulfonated polyetheretherketone membrane.

[0011] The asymmetrically modified silica particles doped with sulfonated polyetheretherketone membranes provided by the present invention have hydroxyl groups on one side of the surface of the asymmetrically modified silica particles, which can form hydrogen bonds with the sulfonated polyetheretherketone, thereby increasing the mechanical stability and thermal stability of the sulfonated polyetheretherketone membranes, while reducing their swelling properties and improving their service life; sulfonic acid groups are grafted on the other side of the surface of the asymmetrically modified silica particles, which can increase the proton conductivity of the sulfonated polyetheretherketone membranes and can improve the performance of liquid flow batteries when used in liquid flow batteries.

[0012] In the present invention, the sulfonated polyetheretherketone can be purchased through market channels or prepared by a synthetic method known in the art. Exemplarily, the preparation method of the sulfonated polyetheretherketone includes: reacting polyetheretherketone with concentrated sulfuric acid, cooling, washing and drying after the reaction to obtain the sulfonated polyetheretherketone; the ratio of polyetheretherketone to concentrated sulfuric acid is 2g:(20-30)mL; the mass percentage concentration of the concentrated sulfuric acid is 98%; the cooling temperature is 15-20°C; the reaction time is 1-2h; the reaction temperature is 50-70°C.

[0013] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0014] As a preferred technical solution, the mass ratio of the surface hydroxylated silica particles to paraffin is 1:(10-20), for example, it can be 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20, etc.

[0015] In the present invention, the surface hydroxylated silica particles can be purchased from the market or prepared by a synthetic method known in the art. Exemplarily, the preparation method of the surface hydroxylated silica particles comprises the following steps:

[0016] (S1) Ammonia water and anhydrous ethanol are mixed and then added dropwise to tetraethyl orthosilicate for reaction to obtain silicon dioxide particles; the mass percentage concentration of the ammonia water is 25%; the volume of the anhydrous ethanol is 90-110 mL; the volume ratio of the ammonia water to the tetraethyl orthosilicate is (10-20):2; and the reaction temperature is 50-70°C.

[0017] (S2) mixing the silica particles obtained in step (1), water, ammonia water and hydrogen peroxide and reacting them to obtain the surface hydroxylated silica particles; the mass percentage concentration of the ammonia water is 25%; the mass percentage concentration of the hydrogen peroxide is 30%; the volume ratio of the water, ammonia water and hydrogen peroxide is (5-7):1:1; the reaction temperature is 70-90°C; and the reaction time is 4-6 minutes.

[0018] Preferably, the first solvent comprises water.

[0019] Preferably, the heating temperature in step (1) is 70-90°C, for example, it can be 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0020] Preferably, the cooling temperature in step (1) is 15-25°C, for example, it can be 15°C, 16°C, 17°C, 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C or 25°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0021] Preferably, the stirring speed is 6000-8000 r / min, for example, it can be 6000 r / min, 6200 r / min, 6400 r / min, 6600 r / min, 6800 r / min, 7000 r / min, 7200 r / min, 7400 r / min, 7600 r / min, 7800 r / min or 8000 r / min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0022] Preferably, the stirring time is 5-15 min, for example, it can be 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0023] As a preferred technical solution, the mercapto-containing silane coupling agent includes γ-mercaptopropyltrimethoxysilane and / or γ-mercaptopropyltriethoxysilane.

[0024] Preferably, the mass ratio of the mercapto-containing silane coupling agent to the surface hydroxylated silica particles is (3-8):1, for example, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1 or 8:1, etc.

[0025] Preferably, the reaction temperature in step (2) is 30-50°C, for example, it can be 30°C, 32°C, 34°C, 36°C, 38°C, 40°C, 42°C, 44°C, 46°C, 48°C or 50°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0026] Preferably, the reaction time of step (2) is 20-28 h, for example, it can be 20 h, 21 h, 22 h, 23 h, 24 h, 25 h, 26 h, 27 h or 28 h, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0027] Preferably, the reaction in step (2) is carried out in the presence of a second solvent.

[0028] Preferably, the second solvent comprises water.

[0029] Preferably, the mass ratio of the second solvent to the paraffin emulsion droplets is (10-15):1, for example, it can be 10:1, 10.5:1, 11:1, 11.5:1, 12:1, 12.5:1, 13:1, 13.5:1, 14:1, 14.5:1 or 15:1, etc.

[0030] As a preferred technical solution, the temperature of the oxidation reaction is 30-50°C, for example, it can be 30°C, 32°C, 34°C, 36°C, 38°C, 40°C, 42°C, 44°C, 46°C, 48°C or 50°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0031] Preferably, the oxidation reaction time is 20-28h, for example, it can be 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h or 28h, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0032] Preferably, the mass percentage concentration of the hydrogen peroxide solution is 30%.

[0033] Preferably, the mass ratio of the hydrogen peroxide solution to the surface hydroxylated silica particles is (2-6):1, for example, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1 or 6:1, etc.

[0034] As a preferred technical solution, after the oxidation reaction is completed, the step of dissolving the paraffin with an organic solvent is also included.

[0035] Preferably, the organic solvent comprises chloroform.

[0036] Preferably, the particle size of the asymmetrically modified silica particles is 190-210 nm, for example, it can be 190 nm, 192 nm, 194 nm, 196 nm, 198 nm, 200 nm, 202 nm, 204 nm, 206 nm, 208 nm or 210 nm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0037] The doping of larger asymmetrically modified silica particles makes the internal channels of the sulfonated polyetheretherketone membrane narrower and more branched, which can reduce the migration speed of larger ions in the membrane and improve the ion selectivity of the membrane.

[0038] As a preferred technical solution, the mass ratio of the asymmetrically modified silica particles and the sulfonated polyetheretherketone is (2.5-20):100, for example, it can be 2.5:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 10:100, 11:100, 13:100, 15:100, 16:100, 18:100 or 20:100, etc.

[0039] As a preferred technical solution, the mixed material in step (3) also includes a third solvent.

[0040] Preferably, the third solvent includes any one of N,N-dimethylformamide, dimethyl sulfoxide or N,N-dimethylacetamide, or a combination of at least two thereof.

[0041] Preferably, the ratio of the sulfonated polyetheretherketone to the third solvent is 1g:(40-60)mL, for example, it can be 1g:40mL, 1g:42mL, 1g:44mL, 1g:46mL, 1g:48mL, 1g:50mL, 1g:52mL, 1g:54mL, 1g:56mL, 1g:58mL or 1g:60mL, etc.

[0042] Preferably, the mixing temperature in step (3) is 50-70°C, for example, it can be 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C or 70°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0043] As a preferred technical solution, the preparation method specifically comprises the following steps:

[0044] (1) Under heating conditions, surface hydroxylated silica particles and paraffin are mixed, water is added, stirred, and then cooled to obtain paraffin emulsion droplets; the mass ratio of the surface hydroxylated silica particles to the paraffin is 1:(10-20); the heating temperature is 70-90° C.; the cooling temperature is 15-25° C.; the stirring speed is 6000-8000 r / min; and the stirring time is 5-15 min;

[0045] (2) mixing the paraffin emulsion obtained in step (1), water and a mercapto-containing silane coupling agent and reacting them to obtain a mixture; mixing the mixture with a hydrogen peroxide solution and then conducting an oxidation reaction, and after the oxidation reaction is completed, adding an organic solvent to dissolve the paraffin to obtain the asymmetrically modified silica particles; the mass ratio of the mercapto-containing silane coupling agent to the surface hydroxylated silica particles is (3-8):1; the reaction temperature is 30-50°C; the reaction time is 20-28h; the mass ratio of water to the paraffin emulsion is (10-15):1; the oxidation reaction temperature is 30-50°C; the oxidation reaction time is 20-28h; the mass percentage concentration of the hydrogen peroxide solution is 30%; the mass ratio of the hydrogen peroxide solution to the surface hydroxylated silica particles is (2-6):1; the particle size of the asymmetrically modified surface hydroxylated silica particles is 190-210nm;

[0046] (3) The asymmetrically modified silica particles, a third solvent and sulfonated polyetheretherketone are mixed and dried to obtain the asymmetrically modified silica particles doped with sulfonated polyetheretherketone membrane; the mass ratio of the asymmetrically modified silica particles and the sulfonated polyetheretherketone is (2.5-20):100; the ratio of the sulfonated polyetheretherketone to the third solvent is 1g:(40-60)mL; the mixing temperature is 50-70°C.

[0047] In a second aspect, the present invention provides an asymmetrically modified silica particle doped sulfonated polyetheretherketone membrane, wherein the asymmetrically modified silica particle doped sulfonated polyetheretherketone membrane is prepared by the preparation method described in the first aspect.

[0048] Preferably, the thickness of the asymmetric modified silica particles doped sulfonated polyetheretherketone membrane is 70-90 μm, for example, it can be 70 μm, 72 μm, 74 μm, 76 μm, 78 μm, 80 μm, 82 μm, 84 μm, 86 μm, 88 μm or 90 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0049] In a third aspect, the present invention provides a liquid flow battery, comprising the asymmetrically modified silica particles doped with sulfonated polyetheretherketone membrane as described in the second aspect.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] 1. One side of the surface of the asymmetrically modified silica particles is a hydroxyl group, which can form a hydrogen bond with sulfonated polyetheretherketone, increase the mechanical stability and thermal stability of the membrane, reduce the swelling of the membrane, and improve the life of the membrane. The swelling rate of the membrane can be reduced to 10%-12%;

[0052] 2. Asymmetrically modified silica particles are grafted with sulfonic acid groups on the other side of the surface, which can increase the proton conductivity of the membrane to 0.04-0.05S / cm; as an ion exchange membrane for flow batteries, the energy efficiency of flow batteries is 73%-80%, which can improve the performance of flow batteries;

[0053] 3. The doping of larger asymmetrically modified silica particles makes the internal channels of the sulfonated polyetheretherketone membrane narrower and more branched, which can reduce the migration speed of larger ions in the membrane and improve the ion selectivity of the membrane. DETAILED DESCRIPTION

[0054] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0055] The sources of some components in the embodiments and comparative examples are as follows:

[0056] (1) Surface hydroxylated silica particles: The preparation method is as follows:

[0057] (S1) mixing 15 mL of 25% ammonia water and 100 mL of anhydrous ethanol, and then adding 2 mL of tetraethyl orthosilicate dropwise to react at a temperature of 60° C. After the reaction is completed, the mixture is repeatedly centrifuged and washed with anhydrous ethanol to obtain silica particles;

[0058] (S2) mixing the silica particles obtained in step (1), 60 mL of deionized water, 10 mL of 25% ammonia water and 10 mL of 30% hydrogen peroxide, reacting at 80° C. for 5 min, and after the reaction, repeatedly centrifuging and washing with anhydrous ethanol, and vacuum drying to obtain the surface hydroxylated silica particles;

[0059] (2) Sulfonated polyetheretherketone: The preparation method is as follows: At 400 r / min, 16 g of polyetheretherketone (purchased from VICTREX450PF in the UK) is reacted with 200 mL of concentrated sulfuric acid with a mass percentage concentration of 98%. The reaction temperature is 60°C and the reaction time is 1.5 h. After the reaction is completed, it is poured into cold water at 20°C for cooling, and repeatedly washed until neutral, and then dried to obtain the sulfonated polyetheretherketone.

[0060] Example 1

[0061] An asymmetrically modified silica particle doped sulfonated polyetheretherketone membrane and a preparation method thereof, the preparation method comprising the following steps:

[0062] (1) At 80°C, 0.8 g of surface hydroxylated silica particles was mixed with 12 g of paraffin wax, and then an appropriate amount of deionized water was added. The mixture was stirred at a speed of 7200 r / min for 10 min, and then cooled to 20°C in a cold water bath, and then rinsed with deionized water to obtain paraffin emulsion droplets;

[0063] (2) mixing the paraffin emulsion obtained in step (1), 150 mL of water and 5 g of γ-mercaptopropyltrimethoxysilane, and reacting the mixture at 40° C. for 24 h to obtain a mixture; mixing the mixture with 3 g of a 30% by mass hydrogen peroxide solution, and reacting the mixture at 40° C. for 24 h, adding chloroform to dissolve the paraffin after the reaction, and centrifuging and washing to obtain the asymmetrically modified silica particles, wherein the asymmetrically modified silica particles have a particle size of 202 nm;

[0064] (3) Under stirring conditions at 60° C., 1 g of sulfonated polyetheretherketone was dissolved in 50 mL of dimethyl sulfoxide, and 0.1 g of the asymmetrically modified silica particles obtained in step (2) was added. After being fully dispersed, the mixture was poured into a grooved glass plate and dried to obtain an asymmetrically modified silica particle-doped sulfonated polyetheretherketone membrane, wherein the doping amount of the asymmetrically modified silica particle-doped sulfonated polyetheretherketone membrane was 10%.

[0065] Example 2

[0066] An asymmetrically modified silica particle doped sulfonated polyetheretherketone membrane and a preparation method thereof, the preparation method comprising the following steps:

[0067] (1) At 80°C, 1 g of surface hydroxylated silica particles was mixed with 20 g of paraffin wax, and then an appropriate amount of deionized water was added. The mixture was stirred at a speed of 8000 r / min for 10 min, and then cooled to 20°C in a cold water bath, and then rinsed with deionized water to obtain paraffin emulsion droplets;

[0068] (2) mixing the paraffin emulsion obtained in step (1), 250 mL of water and 8 g of γ-mercaptopropyltrimethoxysilane, and reacting the mixture at 50° C. for 24 h to obtain a mixture; mixing the mixture with 6 g of a 30% by mass hydrogen peroxide solution, and reacting the mixture at 50° C. for 24 h, adding chloroform to dissolve the paraffin after the reaction, and centrifuging and washing to obtain the asymmetrically modified silica particles, wherein the asymmetrically modified silica particles have a particle size of 195 nm;

[0069] (3) Under stirring conditions at 60° C., 1 g of sulfonated polyetheretherketone was dissolved in 50 mL of N,N-dimethylformamide, and 0.2 g of the asymmetrically modified silica particles obtained in step (2) was added. After being fully dispersed, the mixture was poured into a grooved glass plate and dried to obtain an asymmetrically modified silica particle-doped sulfonated polyetheretherketone membrane, wherein the doping amount of the asymmetrically modified silica particle-doped sulfonated polyetheretherketone membrane was 20%.

[0070] Example 3

[0071] An asymmetrically modified silica particle doped sulfonated polyetheretherketone membrane and a preparation method thereof, the preparation method comprising the following steps:

[0072] (1) At 80°C, 1 g of surface hydroxylated silica particles was mixed with 10 g of paraffin wax, and then an appropriate amount of deionized water was added. The mixture was stirred at a speed of 6000 r / min for 10 min, and then cooled to 20°C in a cold water bath, and then rinsed with deionized water to obtain paraffin emulsion droplets;

[0073] (2) mixing the paraffin emulsion obtained in step (1), 150 mL of water and 3 g of γ-mercaptopropyltrimethoxysilane, and reacting the mixture at 30° C. for 24 h to obtain a mixture; mixing the mixture with 2 g of a 30% by mass hydrogen peroxide solution, and reacting the mixture at 30° C. for 24 h, adding chloroform to dissolve the paraffin after the reaction, and centrifuging and washing to obtain the asymmetrically modified silica particles, wherein the asymmetrically modified silica particles have a particle size of 210 nm;

[0074] (3) Under stirring conditions at 60° C., 1 g of sulfonated polyetheretherketone was dissolved in 50 mL of N,N-dimethylacetamide, and 0.025 g of the asymmetrically modified silica particles obtained in step (2) was added. After being fully dispersed, the mixture was poured into a grooved glass plate and dried to obtain an asymmetrically modified silica particle-doped sulfonated polyetheretherketone membrane, wherein the doping amount of the asymmetrically modified silica particle-doped sulfonated polyetheretherketone membrane was 2.5%.

[0075] Comparative Example 1

[0076] A uniformly modified silica particle doped sulfonated polyetheretherketone membrane and a preparation method thereof, the preparation method comprising the following steps:

[0077] (1) 0.8 g of surface hydroxylated silica particles and 5 g of γ-mercaptopropyltrimethoxysilane were mixed and reacted at 40° C. for 24 h to obtain a mixture; the mixture was mixed with 3 g of a 30% by mass hydrogen peroxide solution and reacted at 40° C. for 24 h, and centrifuged and washed to obtain the uniformly modified silica particles;

[0078] (2) Dissolve 1 g of sulfonated polyetheretherketone in 50 mL of dimethyl sulfoxide, add 0.1 g of the uniformly modified silica particles obtained in step (1), and after fully dispersing, pour into a grooved glass plate and dry to obtain the uniformly modified silica particles doped with sulfonated polyetheretherketone film.

[0079] Comparative Example 2

[0080] A sulfonated polyetheretherketone membrane doped with surface hydroxylated silica particles and a preparation method thereof. The preparation method comprises: dissolving 1 g of sulfonated polyetheretherketone in 50 mL of dimethyl sulfoxide, adding 0.1 g of surface hydroxylated silica particles, fully dispersing the particles, pouring the particles into a grooved glass plate and drying the particles, to obtain the sulfonated polyetheretherketone membrane doped with surface hydroxylated silica particles.

[0081] Comparative Example 3

[0082] A surface mercaptolated silicon dioxide particle doped sulfonated polyetheretherketone membrane and a preparation method thereof, which differs from Example 1 only in that in step (2), no hydrogen peroxide solution is added for oxidation reaction, and the rest of the raw materials, process parameters and steps are the same as those in Example 1.

[0083] Comparative Example 4

[0084] A uniformly modified silica particle-doped sulfonated polyetheretherketone membrane and a preparation method thereof, which differs from Example 1 only in that the temperature of the reaction between the paraffin droplets and γ-mercaptopropyltrimethoxysilane and the temperature of the oxidation reaction in step (2) are both 80°C, and the remaining raw materials, process parameters and steps are the same as those in Example 1.

[0085] Comparative Example 5

[0086] An asymmetrically modified silica particle doped sulfonated polyetheretherketone membrane and a preparation method thereof, which differs from Example 1 only in that 0.5 g of asymmetrically modified silica particles are added in step (3), and the remaining raw materials, process parameters and steps are the same as those in Example 1.

[0087] Material characterization and performance testing:

[0088] (1) Particle size test method for asymmetrically modified silica particles: The particles to be tested are placed in an electron beam and the particle size is measured by observing the transmission electron image of the particles using a transmission electron microscope (JEOL Ltd. JEM2001F).

[0089] (2) Test method for membrane swelling rate: Cut the dry and clean film into rectangular samples of equal size (3 cm × 4.5 cm), then completely immerse the samples in deionized water for 24 h, take out the samples and quickly wipe the moisture on the flat surface of the samples with absorbent paper, and quickly measure and record the length after immersion. In order to reduce experimental errors, 3 parallel samples are prepared for each sample for testing, and the arithmetic mean of the obtained values ​​is calculated to obtain the membrane swelling rate. The swelling rate of a single membrane can be calculated using the following formula: Where: L dry and L wet Respectively represent the length of the membrane before and after immersion, and the test results are shown in Table 1;

[0090] (3) Test method for proton conductivity of membrane: Use a resistance meter (Nanjing Daming Instrument Co., Ltd., model DME-20) to test and record the resistance of the device with and without the membrane to be tested. The proton conductivity σ of the membrane to be tested can be calculated by the following formula: Where L is the thickness of the film to be tested, cm; A is the effective area of ​​the film to be tested, cm 2 ; R1 and R2 are the resistance with the film to be tested and the resistance without the film to be tested, Ω, and the test results are shown in Table 1;

[0091] Table 1

[0092] Swelling rate Proton conductivity (S / cm) Example 1 10% 0.05 Example 2 12% 0.043 Example 3 11% 0.04 Comparative Example 1 20% 0.03 Comparative Example 2 15% 0.02 Comparative Example 3 15% 0.02 Comparative Example 4 20% 0.04 Comparative Example 5 - -

[0093] As can be seen from Table 1, the asymmetrically modified silica particles doped with sulfonated polyetheretherketone membrane provided by the present invention has a lower swelling rate and a higher proton conductivity; in the uniformly modified silica particles doped with sulfonated polyetheretherketone membrane provided in Comparative Example 1, no paraffin is added during the preparation process, and the surface of the silica particles is not asymmetrically modified, so the swelling rate of the membrane is relatively high; in Comparative Example 2, since there is no grafted sulfonic acid group on the surface of the silica particles, the proton conductivity of the membrane is poor; in Comparative Example 3, since the thiol groups on the surface of the silica particles are not oxidized to sulfonic acid groups, the conductivity is also poor; in Comparative Example 4, since the reaction temperature in step (2) is too high, the paraffin melts during the reaction and the surface of the silica particles cannot be asymmetrically modified. There are only sulfonic acid groups and no hydroxyl groups on the surface of the silica particles, so the swelling rate of the membrane is relatively high; in Comparative Example 5, since the doping amount of the asymmetrically modified silica particles is too large, there is obvious agglomeration and dissolution phenomenon, which makes the hybrid membrane easy to break and data measurement cannot be performed.

[0094] (4) Energy efficiency test of all-vanadium liquid flow battery: The all-vanadium liquid flow battery comprises a fastening end plate, a current collector, a bipolar plate, a liquid flow frame, a carbon felt electrode and an ion exchange membrane, and is a sandwich symmetrical structure centered on the ion exchange membrane. The asymmetric modified silica particles doped with sulfonated polyetheretherketone membrane provided in Examples 1-3 and the doped sulfonated polyetheretherketone membrane provided in Comparative Examples 1-5 are respectively used as the ion exchange membrane of the all-vanadium liquid flow battery. The battery test adopts the Arbin battery test system. At a current density of 120 mA / cm 2 , the energy efficiency was tested in the voltage range of 0.7-1.75V. The test results are shown in Table 2:

[0095] Table 2

[0096] Energy efficiency Example 1 80% Example 2 75% Example 3 73% Comparative Example 1 61% Comparative Example 2 54% Comparative Example 3 52% Comparative Example 4 70% Comparative Example 5 -

[0097] It can be seen from Table 2 that the use of the asymmetric modified silica particles doped with sulfonated polyetheretherketone membrane provided by the present invention as the ion exchange membrane of the all-vanadium flow battery can effectively improve the energy efficiency of the flow battery. Since the hybrid membrane of Comparative Example 5 is easily broken, it cannot be used in the flow battery, and therefore no experimental data can be measured.

[0098] The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing asymmetric modified silica particles doped with sulfonated polyetheretherketone membrane, characterized in that: The preparation method comprises the following steps: (1) under heating conditions, mixing surface hydroxylated silica particles and paraffin, adding a first solvent, stirring, and then cooling to obtain paraffin emulsion droplets; (2) mixing the paraffin emulsion droplets obtained in step (1) and the mercapto-containing silane coupling agent and reacting them to obtain a mixture; mixing the mixture with a hydrogen peroxide solution and then performing an oxidation reaction to obtain the asymmetrically modified silica particles; (3) The asymmetrically modified silica particles and sulfonated polyetheretherketone are mixed and dried to obtain the asymmetrically modified silica particles doped with sulfonated polyetheretherketone membrane.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the surface hydroxylated silica particles to paraffin is 1:(10-20); Preferably, the first solvent comprises water; Preferably, the heating temperature in step (1) is 70-90°C; Preferably, the cooling temperature in step (1) is 15-25°C; Preferably, the stirring speed is 6000-8000r / min; Preferably, the stirring time is 5-15 min.

3. The preparation method according to claim 1 or 2, characterized in that: The mercapto-containing silane coupling agent includes γ-mercaptopropyltrimethoxysilane and / or γ-mercaptopropyltriethoxysilane; Preferably, the mass ratio of the mercapto-containing silane coupling agent to the surface hydroxylated silica particles is (3-8):1; Preferably, the reaction temperature in step (2) is 30-50°C; Preferably, the reaction time in step (2) is 20-28 hours; Preferably, the reaction in step (2) is carried out in the presence of a second solvent; Preferably, the second solvent comprises water; Preferably, the mass ratio of the second solvent to the paraffin emulsion droplets is (10-15):

1.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The temperature of the oxidation reaction is 30-50°C; Preferably, the oxidation reaction time is 20-28h; Preferably, the mass percentage concentration of the hydrogen peroxide solution is 30%; Preferably, the mass ratio of the hydrogen peroxide solution to the surface hydroxylated silicon dioxide particles is (2-6):

1.

5. The preparation method according to any one of claims 1 to 4, characterized in that: After the oxidation reaction is completed, the step of dissolving the paraffin with an organic solvent is also included; Preferably, the organic solvent comprises chloroform; Preferably, the particle size of the asymmetrically modified silica particles is 190-210 nm.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The mass ratio of the asymmetrically modified silica particles to the sulfonated polyetheretherketone is (2.5-20):

100.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The mixed material in step (3) further comprises a third solvent; Preferably, the third solvent comprises any one of N,N-dimethylformamide, dimethyl sulfoxide or N,N-dimethylacetamide or a combination of at least two thereof; Preferably, the ratio of the sulfonated polyetheretherketone to the third solvent is 1 g: (40-60) mL; Preferably, the mixing temperature in step (3) is 50-70°C.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method specifically comprises the following steps: (1) under heating conditions, surface hydroxylated silica particles and paraffin are mixed, water is added, stirred, and then cooled to obtain paraffin emulsion droplets; The mass ratio of the surface hydroxylated silica particles to paraffin is 1:(10-20); The heating temperature is 70-90°C; The cooling temperature is 15-25°C; The stirring speed is 6000-8000r / min; The stirring time is 5-15min; (2) mixing the paraffin wax emulsion obtained in step (1), water and a mercapto-containing silane coupling agent and reacting the mixture to obtain a mixture; mixing the mixture with a hydrogen peroxide solution and performing an oxidation reaction, and after the oxidation reaction is completed, adding an organic solvent to dissolve the paraffin wax to obtain the asymmetrically modified silica particles; The mass ratio of the mercapto-containing silane coupling agent to the surface hydroxylated silica particles is (3-8):1; The reaction temperature is 30-50°C; The reaction time is 20-28h; The mass ratio of water to paraffin emulsion droplets is (10-15):1; The temperature of the oxidation reaction is 30-50°C; The oxidation reaction time is 20-28h; The mass percentage concentration of the hydrogen peroxide solution is 30%; The mass ratio of the hydrogen peroxide solution to the surface hydroxylated silicon dioxide particles is (2-6):1; The particle size of the asymmetrically modified silica particles is 190-210 nm; (3) mixing the asymmetrically modified silica particles, a third solvent and sulfonated polyetheretherketone and drying the mixture to obtain the asymmetrically modified silica particles doped with sulfonated polyetheretherketone membrane; The mass ratio of the asymmetrically modified silica particles to the sulfonated polyetheretherketone is (2.5-20):100; The ratio of the sulfonated polyetheretherketone to the third solvent is 1 g: (40-60) mL; The mixing temperature is 50-70°C.

9. An asymmetrically modified silica particle doped sulfonated polyetheretherketone membrane, characterized in that: The asymmetrically modified silica particles doped with sulfonated polyetheretherketone membrane is prepared by the preparation method according to any one of claims 1 to 8; Preferably, the thickness of the asymmetrically modified silica particle-doped sulfonated polyetheretherketone membrane is 70-90 μm.

10. A liquid flow battery, characterized in that: The liquid flow battery comprises the asymmetrically modified silica particles doped with sulfonated polyetheretherketone membrane as claimed in claim 9.

Citation Information

Patent Citations

  • Sulfonated poly(ether ether ketone)-sulfonated silicon dioxide microsphere hybrid membrane, as well as preparation and application of membrane

    CN104209023A

  • Sulfonated polyether ether ketone and carboxylated silicon dioxide microsphere hybrid membrane as well as preparation method and application of sulfonated polyether ether ketone and carboxylated silicon dioxide microsphere hybrid membrane

    CN104212153A

  • Sulfonated poly(ether ether ketone)-amination silica microsphere hybrid membrane and preparation and application thereof

    CN104212154A

  • Janus nanoparticle modified by azide groups and preparation method and application of Janus nanoparticle modified by azide groups

    CN111097042A

  • Sulfonated polyetheretherketone proton exchange membrane as well as preparation method and application thereof

    CN114883618A

Cited By

  • Sulfonated PEEK film for hydrogen fuel cell and preparation method of sulfonated PEEK film

    CN120059441A

  • A sulfonated PEEK film for hydrogen fuel cells and a method for preparing the same

    CN120059441B

  • Composite material and manufacturing method thereof, composite coating, appliance and manufacturing method thereof

    CN121537772A